Front Cover: Silica Support‐Enhanced Pd‐Catalyzed Allylation Using Allylic Alcohols (ChemCatChem 20/2018). Issue 20 (24th October 2018) - Motokura, Ken; Ikeda, Marika; Kim, Minjune; Nakajima, Kiyotaka; Kawashima, Sae; Nambo, Masayuki; Chun, Wang‐Jae; Tanaka, Shinji
Abstract : The Front Cover illustrates the concerted catalysis of a Pd complex and silanol on a mesoporous silica surface for the efficient activation of allylic alcohol in the allylation of nucleophiles. In their Full Paper, K. Motokura et al. demonstrate that the Pd‐catalyzed allylation is accelerated by silanol on the support surface: The catalytic activity of the supported Pd complex is around 9 times higher than that of its homogeneous precursor Pd complex. The catalyst has an excellent turnover number of 4500 based on Pd, and wide substrate scope. The detailed catalyst structure and concerted mechanism were analyzed by XAFS and in‐situ FT‐IR. More information can be found in the Full Paper by K. Motokura et al. onpage 4536 in Issue 20, 2018 (DOI:10.1002/cctc.201801097 ).